Landsat imageries in the study of planar surfaces and lineaments in Garhwal Himalaya, India - Prasad, C.; Shandilya, A. K.; Verma, V. K. (Journal of Nepal Geological Society, 1981)
Morphological features are identified and studied on the basis of the interpretations of landsat imageries and topographic maps, aided by field checks in the study area comprising the drainage network of Alaknanda, Mandakini, Bhilanganga rivers in Garhwal Himalaya. Various planar surface, and lineaments are delineated. The studies show that the major lineaments oriented in NNE- SSW, E-W, NW-SE, ENE-WSW, NE- SW, and N-S directions are either fault zones or the zones of fracturing along the major fold axes. The major fault, zones like the Main Central Thrust, Alaknanda fault, Srinagar (North Almora) thrust and Garhwal thrust are represented by NW-SE and E-W trending lineaments, while Mandakini and Bhilanganga zones of fracturing are represented by the NNE-SSW and N-S lineaments. Three distinct levels of planar surfaces have been identified. The summit and middle surfaces exhibit distinct variations in their mean altitudes when placed on the opposite sides of fault zones, which indicate some recent reactivation of these fault zones. On this basis, the Mandakini fracture zone appears to be a reactivated basement fault, which has not been identified so far.